PENGARUH TINGKAT KECERDASAN DAN PENGALAMAN AUDIT TERHADAP KESIAPAN AUDITOR DALAM MENGHADAPI AFTA 2015 (Studi Empiris pada Auditor di Kantor Akuntan Publik Provinsi Bali) - Lestari, I Gst Agung Krisna; Suardikha, I Made Sadha; Dwi Ratnadi, Ni Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.05.TAHUN 2016, 2016)
The Level of auditor comprehension especially in pacing IFRS and audit experience were important thing to know  auditor’s readiness to face 2015 AFTA. Motivation Theory theory purposed by Gibson in 2004 was the main theory. the primary data was used as data collection method in this research in which it was done to 75 of  98 auditor spread in nine KAP located in Bali. This research used multiple linear regression with assistant of SPSS version 17 as analysis data method. The result of this research was that comprehension level had positive impact for auditor’s readiness to face 2015 AFTA, audit experience as well. The conclusion of this research was that auditors having high comprehension level especially in understanding IFRS and having good readiness level, would prefer to have high readiness level to face 2015 AFTA.
Keywords: comprehension level, audit experience, and auditor readiness to face 2015 AFTA